Power of the Press Studies of the Gospel Advocate, The Christian Standard, and the Christian-Evangelist - Hughes, Henry T. (Disciples of Christ Historical Society, 1987)
Based on the 1986 Reed Lectures, Power of the Press illustrates the important role that the Gospel Advocate, the Christian Standard, and the Christian-Evangelist played in shaping the identity of all three streams of the Stone-Campbell Movement in the nineteenth and early twentieth century. The essays also offer explanations as to why publishing offered such remarkable influence in this period.